Circumventricular Organs and Parasite Neurotropism: Neglected Gates to the Brain? - Bentivoglio, Marina; Kristensson, Krister; Rottenberg, Martin E. (Frontiers in Immunology, 2018)
Circumventricular organs (CVOs), neural structures located around the third and fourth ventricles, harbor, similarly to the choroid plexus, vessels devoid of a blood-brain barrier (BBB). This enables them to sense immune-stimulatory molecules in the blood circulation, but may also increase chances of exposure to microbes. In spite of this, attacks to CVOs by microbes are rarely described. It is here highlighted that CVOs and choroid plexus can be infected by pathogens circulating in the bloodstream, providing a route for brain penetration, as shown by infections with the parasites Trypanosoma brucei. Immune responses elicited by pathogens or systemic infections in the choroid plexus and CVOs are briefly outlined. From the choroid plexus trypanosomes can seed into the ventricles and initiate accelerated infiltration of T cells and parasites in periventricular areas. The highly motile trypanosomes may also enter the brain parenchyma from the median eminence, a CVO located at the base of the third ventricle, by crossing the border into the BBB-protected hypothalamic arcuate nuclei. A gate may, thus, be provided for trypanosomes to move into brain areas connected to networks of regulation of circadian rhythms and sleep-wakefulness, to which other CVOs are also connected. Functional imbalances in these networks characterize human African trypanosomiasis, also called sleeping sickness. They are distinct from the sickness response to bacterial infections, but can occur in common neuropsychiatric diseases. Altogether the findings lead to the question: does the neglect in reporting microbe attacks to CVOs reflect lack of awareness in investigations or of gate-opening capability by microbes?